The Effect of Vlog on Students' Speaking Ability at MTsN 1 Kediri - Ahmad Septiyan Nugroho (Graduate Program, University of Islam Malang, 2021)
ABSTRACTThis research aims to determine the effectiveness of vlog media in improving students' speaking abilities better at 7th L students at MTsN 1 Kediri. This research used a design of pre-experimental through one cluster pre-test and post-test. The material provided was a descriptive text. The instrument in pre-test, students are ordered test orally in the class one by one directly, the researcher gives them a topic then the students tell it. while in post-test, students are ordered to make Vlog to speak up by recording. Both of pre-test and post-test must be done about two until five minutes. This research was conducted in 7th L class MTsN 1 Kediri with 20 students as respondents. In this study, data of the research was a test score. The researcher obtained two data from the pre-test and post-test. In this study there were 2 raters. The first rater was a teacher; and the second rater was a researcher. The reliability of this research was inter-rater agreement where there was agreement on the tolerance for different scores between raters. the split score was 2 or more in scale of 1-5. The researcher only used the smaller scores of the split score to be calculated. there are four steps to analyze the data. First, calculating the mean of the scores from the pre-test and post-test. Next, comparing the mean of the pre-test and post-test. Next, calculating the homogeneity test. Lastly, calculating the significance level of the difference in the average data through Paired Sample t-Test. This method is done using SPSS 21. From the analysis above, it could be decided that there was a significant difference in the test results between the pre-test and post-test results of the 14 students that were counted. The students' mean score on the post-test was 92.125 and the mean score from the pre-test was 46.625. The different mean was 45.5 and the significant value was .000. So, the researcher resolved that the use of Vlog was very effective in improving the speaking achievement of 7th L class at MTsN 1 Kediri.